Fostering Critical Thinking and Communication Skills In Students: The Foundation For Lifelong Learning - I, Imelda; N, Nadella; Nadia, Nafisah; Harahap, Salsabila; Amirul, Bani (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The purpose of this study is to identify students’ perception towards English speaking ability. The researcher used descriptive qualitative research as the method in this study. The Observation and interview wereused as the instrument. To increase the validity of the data, field note was used to support the methodology of the research. After analyzing the data, the researcher found thatthe students’ perception toward English speaking ability is various. They realizedthat speaking is an important skill in English to be mastered well. They argued that speaking is important skill to communicate each other especially as the International and global language used in the world. Unfortunately, most of them could not speak English well and fluently, and many students also considered that speaking is difficult to be mastered because of some aspects such as limited vocabulary, less understanding of grammar and also the pronunciation which cannot be well. The result also showed that there are some themes drawn from the interview, namely students’ difficulties, students’ expectation and need of teacher’s assistance